Math Learning Outcomes with Cooperative Learning Model (STAD) Reviewed from Students’ Self Efficacy - Alifi Nur Hidayah; Kertono Kertono; Suciati Suciati (AlphaMath : Journal of Mathematics Education, 2023)
This study aims to determine the effectiveness of the STAD cooperative learning model in terms of students' self-efficacy towards mathematics learning outcomes, particularly in the topics of Least Common Multiple (KPK) and Greatest Common Divisor (FPB), for fourth-grade students at SD Negeri Manyaran 02, divided into two learning groups: Class IV.A with 25 students and Class IV.B with 24 students. The research design employed in this study is quasi-experimental. Quasi-experimental research is conducted under conditions that do not allow for full control. Data collection utilized questionnaire and test techniques, followed by data analysis using a two-way ANOVA and further post hoc tests (multiple comparisons). Based on the tests, the test instrument was declared valid, with difficulty index reaching ???? < 0.30 for difficult criteria and ???? > 0.70 for easy criteria, as well as a reliability index of ????11 > 0.70. The study findings indicate that there is no significant effect of the STAD cooperative learning model on mathematics learning outcomes when viewed from the self-efficacy of fourth-grade students. However, the relationship between the STAD model and self-efficacy in mathematics learning outcomes shows positive results. Students with higher self-efficacy indices are proven to have better learning outcomes compared to those with lower self-efficacy levels.